1995
DOI: 10.1002/eji.1830251008
|View full text |Cite
|
Sign up to set email alerts
|

Human CD6 possesses a large, alternatively spliced cytoplasmic domain

Abstract: Human CD6 is a monomeric 105/130-kDa T cell surface glycoprotein that is involved in T cell activation. The apparent discrepancy between the size of the cytoplasmic domain in human (44 amino acids) and mouse (243 amino acids) CD6, led us to use reverse transcriptase-polymerase chain reaction of human peripheral blood lymphocyte mRNA to isolate cDNA clones that include the carboxyl-terminal coding region of human CD6. The nucleotide sequence of the longest human cDNA clone, CD6-PB1, predicts a protein of 668 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…CD5 and CD6 both contain several tyrosine residues in their cytoplasmic regions, the tail of CD6 being remarkably long (244 amino acids), with nine tyrosine residues (7,33). Initial studies with CD5 and CD6 monoclonal antibodies (mAbs) suggested a positive regulatory role for these proteins in regulating T-cell responses (1,38).…”
mentioning
confidence: 99%
“…CD5 and CD6 both contain several tyrosine residues in their cytoplasmic regions, the tail of CD6 being remarkably long (244 amino acids), with nine tyrosine residues (7,33). Initial studies with CD5 and CD6 monoclonal antibodies (mAbs) suggested a positive regulatory role for these proteins in regulating T-cell responses (1,38).…”
mentioning
confidence: 99%
“…In fact, CD6 expression correlates with thymocyte-positive selection and resistance to apoptosis (15). CD6 possesses a long cytoplasmic domain well suited for signal transduction (23), but the intracellular consequences of CD6 engagement by its ligand are mostly unknown. It has been shown, however, that TCR/CD3 stimulation induces tyrosine phosphorylation of CD6 (11,12), which might then promote recruitment of signaling molecules and contribute to building the IS.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic domain of CD6 is unusually long and also contains two well-conserved proline-rich sequences, which are potential binding sites for SH3 domain-containing proteins well suited for signal transduction (16,18). Indeed, the rat homolog of CD6 has been shown to associate with protein tyrosine kinases of different families, namely Src-family kinases Lck and Fyn, Zap70 of the Syk family, and the Tec-family kinase Itk (19).…”
mentioning
confidence: 99%